Laboratory trials on the toxicity of hydramethylnon (Amdro; AC 217,300) to Reticulitermes santonensis Feytaud (Isoptera: Rhinotermitidae) and Microtermes lepidus Sjöstedt (Isoptera: Termitidae) - Logan, James W. M.; Abood, Faizah (1990)
The amidinohydrazone insecticide hydramethylnon, exhibited delayed toxicity to workers of Reticulitermes santonensis Feytaud and Microtermes lepidus Sjöstedt over a range of concentrations, with deaths starting two to six days after exposure. R. santonensis workers which had been exposed to hydramethylnon passed the insecticide to untreated termite workers, larvae and nymphs by trophallaxis. Laboratory colonies of R. santonensis exposed to hydramethylnon were killed completely within 20 days. The possible use of hydramethylnon impregnated baits for the control of subterranean termites is discussed. © 1990, Cambridge University Press. All rights reserved.